Lymph node Yield in Apical Tissue During Triangle Operation While Doing Whipples Operation: An Observational Study - Dhiresh Kumar Maharjan; Prashant Pudasaini; Bidur Prasad Acharya; Yugal Limbu; Roshan Ghimire; Prabin BIkram Thapa (Journal of Nepal Medical Association)
Introduction: The "TRIANGLE operation" involves the en-bloc removal of the tumor and the entire "mesopancreas" from the triangle-shaped space bounded by the superior mesenteric artery, coeliac trunk, and portal vein. This study assessed lymph node yield in apical tissue during the triangle operation. Methods: An observational cross-section study was conducted for two years at the Department of Gastrointestinal and General Surgery at a tertiary care center of Nepal. from 15th March 2022 to 15th March 2024. The operative procedure included pancreaticoduodenectomy or Whipple’s operation. Total sampling was done. Postoperative outcome and lymph node yeild of the surgeries were studied. Ethical approval was taken from the Institutional Review Committee (Reference No-1102202204). Results: A total of 56 patients underwent pancreaticoduodenectomy along with a triangle operation. The mean age of the patients was 56.38±14.79 years. Male: Female ratio was 1.2:1. Mean preoperative BMI was 24.41±4.72. The mean total lymph node yield was 20.95±8.57. Nineteen patients had a positive lymph node yield in the triangle tissue. The mean triangle lymph node yield was 10.59±4.92, and the mean positive lymph node was 2.58 ±1.64. Among 56 patients, nine patients had both apical margin and the rest of the triangle tissue margin positive. Ten patients had negative apical tissue margins, but the rest of the triangle tissue was positive, whereas, in thirty-seven patients, both the apical tissue and the rest of the triangle circumferential resection margin tissue were negative. Conclusions: This study emphasizes the importance of the inclusion of apical tissue dissection at the confluence of SMA and coeliac trunk to achieve R0 resection. However, a long-term follow is awaited.